Implementation of the Principle of Nationality in Sales and Purchases Through Nominee Agreements Regarding Land Rights In Indonesia - Hartadi, Didit (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research analyzes the complexity of applying the principle of nationality in buying and selling land rights in Indonesia, especially regarding the practice of nominee agreements. This principle, which limits land ownership to Indonesian citizens and national legal entities, is often circumvented by nominee agreements where Indonesian citizens act as formal owners, but substantive control is in the hands of foreign parties. The research results show that this practice is legal smuggling which is detrimental to agrarian sovereignty, creates legal uncertainty, and has the potential to trigger abuse. Therefore, stronger law enforcement, strict supervision and strict sanctions are urgently needed to maintain the integrity of the principle of nationality and prevent similar practices in the future.